Enhancing the low temperature water–gas shift reaction through a hybrid sorption-enhanced membrane reactor for high-purity hydrogen production. (1st November 2015) - Soria, M.A.; Tosti, S.; Mendes, A.; Madeira, Luis M.
Graphical abstract: Highlights: Multifunctional sorption-enhanced membrane reactor. The coexistence of both the membrane (H2 separation) and the CO2 sorbent act simultaneously. The WGS equilibrium is completely shifted allowing to obtain two ultra-pure H2 streams. Process integration by combining CO2 and H2 removal in a single unit is beneficial for H2 production. Abstract: The low temperature water–gas-shift reaction (LT-WGS) has been assessed by means of a hybrid sorption-enhanced membrane reactor (HSEMR) that combines both CO2 and H2 removal from the reaction zone. The performance of this reactor has been compared with that obtained by (i) a traditional and (ii) a sorption-enhanced (only CO2 is removed) reactor operating in the same operational conditions. Cu/ZnO–Al2 O3 and K2 CO3 -promoted hydrotalcite materials have been used as a catalyst and CO2 sorbent, respectively. A self-supported Pd–Ag membrane tube has been used in order to selectively separate the H2 . The CO2 sorption capacity, in the presence and absence of water vapour, of the potassium-promoted hydrotalcite has been determined by means of breakthrough experiments. The presence of water vapour enhanced the sorption capacity of the hydrotalcite in the experimental conditions used. Concerning the performance of the HSERM, results clearly show that when both CO2 and H2 are removed from the reaction zone, the hydrogen production through the reversible LT-WGS reaction is enhanced compared to either a traditional or a sorption-enhanced reactor, allowing overcoming equilibrium limitations and obtain a pure H2 stream.